Penyusunan Indeks Kemasyarakatan di Kota Bandung - Essa, Wiedy Yang (Research and Development Agency Ministry of Home Affairs, 2018)
Bandung as a metropolitan city is faced with social problems, one of which is the diminishing value of social capital which has an impact on weak community participation in development. The Bandung City social index is a measure or value that describes the social capital of the city of Bandung and is expected to be the basis for policy formulation in response to various social challenges. However, social index measurement instruments have not been studied, so this study was conducted to compile Bandung City social index measurement instruments with valid and reliable variables and analyze the implementation process of the index measurement policy in the field. Social capital is a key concept in the formulation of a social index that is at the level of the micro aspect of â€œjoint actionâ€ in the form of community participation. The research method uses mix methods where quantitative in testing the validity and reliability of instruments, qualitative in formulating indicators and analyzing constraints through in-depth interviews and FGDs with key stakeholders, conducted in the city of Bandung. Measurement instruments are obtained by synthesis of various theories and measurements of global and national social capital, discussed in the FGD, and tested for their validity and reliability. The results show variables of social capital with 15 indicators in 5 dimensions, namely participation, mutual trust, social norms and shared values, mutual respect, and relationships. The main obstacle faced in the process of implementing social index measurement policies is that substantially the measurement can be multi-interpretive, methodologically and psychologically vulnerable to subjectivity bias, and unpreparedness of human resources. The anticipation of various obstacles can be overcome through empowerment and active involvement of neighborhoods heads and socialization in the region.